(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Organ donation is a vital medical procedure that saves thousands of lives worldwide. However, in Pakistan, the rate of organ donation remains very low due to lack of awareness, cultural beliefs, and misconceptions. Nursing students are future healthcare providers and play an important role in educating the community; therefore, their awareness and beliefs strongly influence public attitudes. Aim: The aim of this study was to assess the awareness and beliefs about organ donation among nursing students in Peshawar and to identify the barriers that affect their willingness to donate. Methodology: A descriptive cross-sectional study was conducted among nursing students in selected nursing colleges of Peshawar. Data were collected using a structured questionnaire covering demographics, awareness, beliefs, and misconceptions. Descriptive statistics (frequencies, percentages, and mean scores) were used for analysis, while inferential tests were applied where appropriate. Results: The findings showed that most nursing students had moderate awareness regarding organ donation. While many students expressed positive beliefs about the importance of donating organs, a significant proportion still reported misconceptions related to religion, fear of body disfigurement, and lack of trust in the healthcare system. Higher awareness was associated with more positive beliefs, whereas misconceptions were linked to decreased willingness to donate. Conclusion: Although nursing students in Peshawar possessed basic awareness of organ donation, misconceptions and cultural barriers negatively affected their beliefs and willingness to donate. Strengthening educational programs, integrating organ donation topics into the curriculum, and conducting awareness sessions can significantly improve knowledge and promote positive attitudes toward organ donation among future healthcare professionals.